Implementasi Konsep Monggo Pinarak dalam Perancangan Interior Pusat Wisata Seni dan Budaya Bojonegoro - Valeska Sidney Irawan; Diana Thamrin; Celline Junica Pradjonggo (Intra, 2019)
Bojonegoro is a district from East Java which has a Geoparak tourism destination and a lot of local potentials that can be developed. However, there is no place for art culture, culinary, and agrotourism communities, also introduction to the local potential, which makes people only transit the city and not knowing about those local potentials in that city. The purpose of this design is to make a place for all the existing art, culinary, and agrotourism communities by designing a philosophic place as an innovation design to introduce the local potentials of Bojonegoro, and to attract local tourists and international tourists, also a place for education which makes use of natural resources as a local festival place which preserves culture. The method used in this design process is a design thinking development, HPI School of Design Thinking, by adding an implementation method to create innovation and excellence value in a design. The step of design thinking are Understanding, Observation, Point of View, Ideation, Prototype, Test, and Implementation. The result of this design is an art and cultural center of Bojonegoro with Monggo Pinarak concept which applies the legend, art and culture of Bojonegoro. This concept application is also used as a special expression for the visitors to come and apply the ambience through personal experience from the cultural elements.